Facility Layout Design at ‘MIRASA’ Crackers SMEs Using Systematic Layout Planning Method and Blocplan Algorithm - Meiliati, Herriyzka; Nazaruddin, Nazaruddin; Ihsan Hamdy, Muhammad; Nur, Muhammad; Suherman, Suherman (INTECOMS: Journal of Information Technology and Computer Science, 2025)
The cracker industry is a food processing industry that is spread across various regions in Indonesia, one of which is Small and Medium Industry (SMEs) Crackers ‘MIRASA’ Pekanbaru. At SMEs MIRASA Crackers there is a layout placement that is not in accordance with the production flow. This causes a decrease in productivity in SMEs where production activities become inefficient so that it takes a lot of time in the production process and there are bottlenecks at several stations. In designing the layout in this study, the Systematic Layout Planning (SLP) and BLOCPLAN methods were used to produce a systematic and efficient layout in increasing productivity and minimising distance transfer at MIRASA Crackers. The results of the calculation of the total displacement distance with the Systematic Layout Planning (SLP) method are 40.86 metres and 47.39 metres, while BLOCPLAN is 43.21 metres. From the results of these calculations, it is known that the proposed layout using the SLP method can minimise the path distance from the initial layout of 61.67 meters with a difference of 20.81 meters.